Numerical investigation on the fluid flow and heat transfer in electroslag remelting furnace with triple-electrode. (7th February 2018) - Ren, N.; Li, B. K.; Li, L. M.; Qi, F. S.; Liu, Z. Q.
Abstract : Electroslag remelting (ESR) furnace with triple-electrode is always used to produce large ingots and the process complexity makes the application not widely spread. Thus, a transient three-dimensional coupled model in industrial scale has been developed to investigate the coupled magneto-hydrodynamics two-phase flow and heat transfer in system. Different from the previous studies with multi-electrode, the current work reveals the triple-electrode ESR with the formation of metal droplets and the solidification of liquid metal. Compared with single-electrode system with the same fill ratio, the heat source in the slag pool with triple-electrode is much more dispersive, and the U-shape metal pool in the ESR furnace with triple-electrode is much shallower and flatter than the V-shaped one in the single-electrode system. A shorter distance from each electrode to the center of system brings a higher heat efficiency, as well as a deeper and narrower metal pool.